The cost-utility of dabigatran etexilate compared with warfarin in treatment and extended anticoagulation of acute VTE in the UK - Jugrin, Anamaria Vera; Ustyugova, Anastasia; Urbich, Michael; Lamotte, Mark; Sunderland, Tom (Thrombosis and Haemostasis, 2015)
The relative efficacy and safety of dabigatran etexilate and warfarin have been evaluated in two head-to-head, phase III, treatment of acute venous thromboembolism (VTE) trials, and one extended prophylaxis trial, in patients with high risk of recurrent VTE. Dabigatran etexilate demonstrated similar efficacy to warfarin, and was associated with a reduced risk of major or clinically relevant bleeds. Based on results of these trials, and real-life disease prognosis following discontinuation of anticoagulation treatment, we evaluated the cost-utility of dabigatran etexilate compared with warfarin in six months anticoagulation, and in extended, up to 24 months anticoagulation, in patients with acute VTE, acute deep-vein thrombosis (DVT) or acute, symptomatic, pulmonary embolism (PE). Costs were analysed from the perspective of the National Health Services (NHS) and Public Social Services (PSS) in England and Wales. Outcomes were quantified in quality-adjusted life years (QALY). The estimated incremental, lifetime cost/QALY gain following acute, symptomatic VTE (DVT or PE) was £1,252/QALY when dabigatran etexilate or warfarin were administered for up to six months treatment. In treatment of acute, symptomatic PE and in DVT respective ratios were £1,767/QALY and £1,075/QALY. In extended, up to 24 months anticoagulation, dabigatran etexilate projected costs/QALY of £8,242/QALY, when compared with warfarin. Results obtained herein were robust across a number of sensitivity analyses and suggest dabigatran etexilate to be a cost-effective alternative to current standard of care when evaluated in six months treatment and in extended anticoagulation following acute VTE (DVT and/or PE).
Keywords: Venous thrombosis; anticoagulation; treatment; cost-effectiveness; economics